(untitled) (Journal of Universal Science Research, 2025)
This article explores speech development in children with Autism Spectrum Disorder (ASD), focusing on the challenges posed by social, neurological, and sensory factors. It examines how these factors impact language acquisition and proposes a comprehensive framework for understanding and supporting speech development in children with ASD.